Complexation of 4-N,N-dimethylaminopyridine with Tin(II), Uranium(IV) and Thorium(IV) - Gilbert, G.J.; Narayanan, S.; Sunitha, S.; Panchanatheswaran, K. (Asian Journal of Chemistry, 2010)
The reactions of 4-N,N-dimethylaminopyridine with SnCI2, UCL4 andTh(NO3)4 result in the formation of complexes in which coordinationoccurs through heterocyclic nitrogen.